Pleural Mesothelioma: Asbestosis-Related Pathogenesis: Mesothelioma Pleura : Patogenesis Terkait Asbestosis - Adityo Wibowo (CV. Jasa Sukses Abadi, 2023)
Pleural mesothelioma is a malignancy that develops from the pleura's mesothelial layer. Pleural mesothelioma is classified into three distinct categories of cells, which have different prognoses. This condition can be caused by different kinds of sources, one of which is chronic exposure to asbestos that enters the airways and causes asbestosis. Asbestos is the main carcinogen related to pleural malignancy. In most cases of pleural mesothelioma, asbestos exposure occurs over a 30-year period. The accumulation of asbestos fiber in the pleural cavity will induce chronic inflammation and abnormal tissue repair. Asbestos is a silicate mineral found in various forms, including chrysotile, crocidolite, amosite, anthophyllite, actinolite and tremolite. Asbestosis can be developed through both direct and indirect exposure. The most frequent causes of asbestosis and pleural mesothelioma are direct asbestos exposure at the workplace and domestic exposure around the environment. The greater risk factors for pleural mesothelioma are directly correlated to high concentration and long duration of exposure. Further study is needed to understand the pathophysiology and immunological pathways that lead to the development of pleural mesothelioma from asbestosis. Significant amounts of exposure have been associated with increasing risk factors for pleural mesothelioma.